ChemInform Abstract: Preparation of 2H‐5, 6‐Dihydroselenines Using α‐Alkoxy Carbonylselenoacetamide. Issue 32 (August 2015) - Ohnuma, Akira; Nagata, Tomohiro; Komura, Kenichi; Ando, Hiromune; Ishihara, Hideharu; Koketsu, Mamoru
Abstract and α, β‐unsaturated ketones